Health, Health-System and Economic Development: A South Asian Perspective (Indian Journal of Public Health Research & Development, 2022)
This study investigates the linkages between health and economic development focusing the seven South Asian(SA) countries for the period of 2000-15. Firstly, a situation analysis of major health indicators indicates that SAcountries are advancing well in life expectancy, mortality and fertility rate while the burden of diseases is shiftingfrom infectious diseases to noncommunicable diseases. The study finds that private sources mainly out of pockethealth expenditure dominates the total spending on health care. Using the linear regression method, the researchalso finds that health expenditure growth is positively correlated with Nominal GDP growth in this region. Thisstudy also discusses the health facility situations and finds that health workforce deficiency challenge is criticalin SA countries. This research also recommends that closing gaps in primary care, strengthening accessibility ofhealth care and making progress in health determinants are necessary to expand Universal Health Coverage (UHC)in the SA region. Finally, the study has listed the major policy interventions in the SA countries and highlighted acouple of areas to be addressed for health sector advancement.
Keywords: Health system, south asia, Health, economic development